Cover Feature: Tailored Lipid Monolayers Doped with Gold Nanoclusters: Surface Studies and Electrochemistry of Hybrid‐film‐covered Electrodes (ChemElectroChem 9/2022). Issue 9 (30th March 2022) - Wieckowska, Agnieszka; Jablonowska, Elzbieta; Dzwonek, Maciej; Jaskolowski, Marcin; Bilewicz, Renata
Abstract : The Cover Feature illustrates the biological–nonbiological hybrid monolayer composed of lipids and gold nanoclusters, Au25 (SC4 )18 0 prepared at the air ‐ water interface and transferred onto ITO surface. The Langmuir–Blodgett technique allows to design the mixed monolayer composition and together with AFM and electrochemistry shows the changes of the lipid monolayer organization and properties upon increasing dilution of the AuNCs sites in the lipid matrix. More information can be found in the Research Article by A. Wieckowska, E. Jablonowska, M. Dzwonek, M. Jaskolowski and R. Bilewicz .